Pyogenic Liver Abscess of Biliary Origin: The Existing Problems and Their Strategies - Shi, Shao-hua; Zhai, Zheng-long; Zheng, Shu-sen (Seminars in Liver Disease, 2018)
Pyogenic liver abscess (PLA) of biliary origin in Southeast Asia mainly occurs in patients with intrahepatic bile duct stone (IBDS) and extrahepatic bile duct stone (EBDS), bilioenteric anastomosis, or biliary stent. IBDS, as an endemic to Southeast Asia, remains a frequent etiology of acute cholangitis and PLA. PLA related to IBDS is characterized by high incidences of PLA recurrence and death related to infection, and difficulties in diagnosis of concomitant cholangicarcinoma. PLA of biliary origin is more likely caused by Escherichia coli, more often presented as polymicrobial infections, and more associated with extended-spectrum β-lactamase (ESBL)–producing Enterobacteriaceae isolates. In this review, the authors summarize the differences on the presumed causes, pathogens, multidrug resistance, treatment, and prognosis of PLA between biliary origin and cryptogenic origin, the latter serving as a first and foremost presumed etiology of PLA. The authors also discuss the existing problems on early diagnosis of concomitant cholangicarcinoma related to IBDS.
Keywords: pyogenic liver abscess; abnormal communication between bile duct and gut; intrahepatic bile duct stone; concomitant cholangiocarcinoma; prognosis